Does Reducing Clerkship Lengths by 25% Affect Medical Student Performance and Perceptions?. (December 2018) - Monrad, Seetha U.; Zaidi, Nikki L. Bibler; Gruppen, Larry D.; Gelb, Douglas J.; Grum, Cyril; Morgan, Helen K.; Daniel, Michelle; Mangrulkar, Rajesh S.; Santen, Sally A.
Abstract : Purpose: Transforming a medical school curriculum wherein students enter clerkships earlier could result in two cohorts in clerkships simultaneously during the transition. To avoid overlapping cohorts at the University of Michigan Medical School, the length of all required clerkships was decreased by 25% during the 2016–2017 academic year, without instituting other systematic structural changes. The authors hypothe sized that the reduction in clerkship duration would result in decreases in student perfor mance and changes in student perceptions. Method: One-way analyses of variance and Tukey post hoc tests were used to compare the 2016–2017 shortened clerkship cohort with the preceding traditional clerkship cohorts (2014–2015 and 2015–2016) on the following student outcomes: National Board of Medical Examiners (NBME) subject exam scores, year-end clinical skills exam scores, evaluation of clerkships, perceived stress, resiliency, well-being, and perception of the learning environment. Results: There were no significant differences in performance on NBME subject exams between the shortened clerkship cohort and the 2015–2016 traditional cohort, but scores declined significantly over the three years for one exam. Perceptions of clerkship quality improved for three shortened clerkships; there were no significant declines. Learning environment perceptions were not worse for the shortened clerkships. There were no significant differences in performance on the clinical skills exam or in perceived stress, resiliency, and well-being. Conclusions: The optimal clerkship duration is a matter of strong opinion, supported by few empirical data. These results provide some evidence that accelerating clinical education may, for the studied outcomes, be feasible. Abstract : Supplemental Digital Content is available in the text.